PERSEPSI SISWA TERHADAP PEMBELAJARAN TEROMPET DALAM KEGIATAN EKSTRAKURIKULER MARCHING BAND: STUDI DESKRIPTIF PADA PESERTA AKTIF DAN NONAKTIF DI SMA NEGERI 3 PADANG - Rivan Sihombing, Rivan Sihombing; alrizkahairidilfa@unp.ac.id2 (Universitas Negeri Padang, 2026)
Marching band extracurricular activities become a medium for students to develop musical skills, discipline, cooperation, and responsibility. One of the important instruments in marching band is the trumpet, which requires mastery of breathing techniques, embouchure, articulation, and body coordination. This study aims to describe students’ perceptions of trumpet learning in marching band extracurricular activities among active and inactive participants at SMA Negeri 3 Padang. This study used a quantitative descriptive approach with survey methods. The population consisted of 30 students participating in trumpet learning activities in the extracurricular marching band program. The sampling technique used purposive sampling by grouping students into active and inactive participants. Data was collected through questionnaires, observation, interviews, and documentation. The results showed that students’ perceptions of trumpet learning were generally in the good category. Positive perceptions were influenced by learning materials, learning methods, the role of coaches and instructors, facilities and environment, as well as the benefits and students’ interest in continuing learning. Active participants tended to have more positive perceptions because they were more involved in practice activities and experienced better skill development compared to inactive participants.